Adaptation of Bandung Masagi Local Wisdom Values in Literature Learning in Elementary School - Dirgantari, Nadilla; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Literature is considered to contain things that can form a noble personality and instill a sense of sensitivity in children and the introduction of regional culture through folklore which is included in cultural heritage. However, in introducing literature to elementary school students, there are obstacles, including the limited literature reading books that are suitable for students. In this regard, researchers are interested in research to determine the value of Bandung Masagi's local wisdom in learning literature through folklore in elementary schools. So the formulation of this research is (1) What is the scope of literature learning material that is relevant to Bandung Masagi's grades in elementary school?; (2) What is the value of Bandung Masagi's local wisdom in the book Collection of Folklore of West Java Province?; (3) How is the implementation of Bandung Masagi values in learning literature in elementary schools?. This article aims to examine what materials are included in the Indonesian language curriculum in elementary schools, describe the results of research on the value of Bandung Masagi local wisdom contained in the book of Collection of Folklore of West Java Province, and its implementation in learning literature in elementary schools using a qualitative approach and content analysis. The researcher recommends these five creative steps in orientation, exploration, creation, presentation, and evaluation in utilizing the values of Bandung Masagi's local wisdom in learning literature in elementary schools.